Bone marrow‐derived fibroblast migration via periostin causes irreversible arthrogenic contracture after joint immobilization. Issue 5 (31st March 2023) - Iura, Hirotaka; Kobayakawa, Kazu; Saiwai, Hirokazu; Konno, Daijiro; Tanaka, Masatake; Hata, Kazuhiro; Tamaru, Tetsuya; Haruta, Yohei; Ono, Gentaro; Kitade, Kazuki; Kijima, Ken; Kubota, Kensuke; et al.
Abstract: Joint contracture causes distressing permanent mobility disorder due to trauma, arthritis, and aging, with no effective treatment available. A principal and irreversible cause of joint contracture has been regarded as the development of joint capsule fibrosis. However, the molecular mechanisms underlying contracture remain unclear. We established a mouse model of knee joint contracture, revealing that fibrosis in joint capsules causes irreversible contracture. RNA‐sequencing of contracture capsules demonstrated a marked enrichment of the genes involved in the extracellular region, particularly periostin ( Postn ). Three‐dimensional magnetic resonance imaging and immunohistological analysis of contracture patients revealed posterior joint capsule thickening with abundant type I collagen ( Col1a2 ) and POSTN in humans. Col1a2‐GFP TG ; Postn − /− mice and chimeric mice with Col1a2‐GFP TG ; tdTomato TG bone marrow showed fibrosis in joint capsules caused by bone marrow‐derived fibroblasts, and POSTN promoted the migration of bone marrow‐derived fibroblasts, contributing to fibrosis and contracture. Conversely, POSTN‐neutralizing antibody attenuated contracture exacerbation. Our findings identified POSTN as a key inducer of fibroblast migration that exacerbates capsule fibrosis, providing a potential therapeutic strategy for joint contracture. Abstract : In immobility‐induced joint contractures, fibrosis of the joint capsule causes irreversible joint contractures, and bone marrow‐derived fibroblasts are increased in the fibrotic joint capsule. POSTN promotes the migration of bone marrow‐derived fibroblasts and contributes to fibrosis and joint contracture in the joint capsule, and deficiency of POSTN attenuates exacerbation of joint contracture.